Adaptive path following control for Wave gliders in time-varying environment. (15th December 2020) - Sun, Xiujun; Zhou, Ying; Sang, Hongqiang; Yu, Peiyuan; Zhang, Shuai
Abstract: Path following control plays an essential role in improving accuracy of navigation and achieving a smooth motion control. However, the performance will exhibit large lateral errors caused by weak maneuverability, large time-lag, and large ocean current disturbance when the wave glider is gliding with a low and time-varying speed. An adaptive path following control integrated an adaptive line-of-sight (ALOS) algorithm and an improved artificial potential field (IAPF) algorithm was put forward in this paper, which could extremely guarantee path following accuracy. The adaptive control based a LOS was introduced to dynamically adjust a parameter of the LOS so that the output desired heading of the wave glider was on-time updated based on the velocity of the wave glider and path following error. The IAPF was applied to analyze and modify the output of the ALOS guiding the vehicle always convergent to the desired path, which could make a real time self-diagnosing, monitoring and correction in path following control. Following this, a closed-loop control was put forward with a dynamic model of the "Black Pearl" wave glider and the given path following control. The proposed control was verified by simulations and sea trials compared with conventional LOS, which demonstrated its effectiveness and long-term reliability. Highlights: Adaptive path following control was for maneuverability, current disturbance. An adaptive LOS control was performed to dynamically adjust the desired heading. An IAPF was used for self-diagnosing, monitoring and control output correction. Simulations and sea trials of a closed-loop motion control system were put forward.